Does Indonesian Bankruptcy Law Protection for Curators in Bankruptcy? - Ahmad Dwi Nuryanto; Mohammed AlHadi Ibrahim Bosha Ahmed (Lembaga Contrarius Indonesia, 2026)
A curator is someone who is appointed by the court to manage and organize the bankruptcy assets of the debtor in carrying out his duties must be in accordance with applicable laws and regulations. When carrying out their duties, curators must be independent and have no conflict of interest with either the debtor or creditors as stipulated in the provisions of Article 15 paragraph 3 of Law Number 37 of 2004. For this reason, the following problems can be formulated, why the burden of the curator's performance in carrying out the bankruptcy estate needs legal protection for the curator, what are the inhibiting factors or threats to the curator in the bankruptcy estate and how to reconstruct the regulation of legal protection of the curator in carrying out the bankruptcy estate. The writing of this dissertation aims to analyze and find the burden of the curator's performance in carrying out the administration of bankruptcy property needs legal protection for the curator, to analyze and find inhibiting factors or threats to the curator in the administration of bankruptcy property, to analyze and find the reconstruction of legal protection for the curator in carrying out the administration of bankruptcy property in order to realize justice-based sustainability. This type of research used is normative legal research, namely legal research conducted by breaking down legal issues and at the same time providing prescriptions. The research used is descriptive analytical. Thus, the need for immunity rights implicitly regulated in the law in order to protect curators in carrying out the administration of bankruptcy assets in order to create justice for all parties in bankruptcy. reconstruction of legal protection regulations for curators in carrying out the administration of bankruptcy assets is to add a new norm formulation to Article 69 of the Bankruptcy Law by strengthening the role of curators in the management and administration of bankruptcy assets, adding immunity rights and / or legal assistance by curator professional organizations and state institutions when curators are reported in suspected criminal acts.